2011
DOI: 10.1016/j.leukres.2010.06.017
|View full text |Cite
|
Sign up to set email alerts
|

JAK2V617F allele burden in polycythemia vera correlates with grade of myelofibrosis, but is not substantially affected by therapy

Abstract: In a series of 105 patients with polycythemia vera, we retrospectively determined whether the JAK2V617F mutation correlated with severity of disease phenotype. Higher JAK2V617F allele burden correlated with more advanced myelofibrosis, greater splenomegaly, and higher white blood cell count, but not with age, gender, hematocrit level, or frequency of phlebotomy prior to cytoreductive therapy. Although a subgroup at increased risk for thrombosis was not clearly defined, there was a suggestion that frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 24 publications
6
38
0
2
Order By: Relevance
“…In a previous study [21], we found that MPL mutated ET patients had greater likelihood of transforming to PET-MF compared to other genotypes, but due to small number of events such difference did not reach the significance level; more recently, Elala et al reported shorter myelofibrosis-free survival in MPL mutated ET patients that remained significant in multivariate analysis, thereby corroborating our current findings [33]. On the other hand, results of this study validate and extend previous observations concerning the role of accumulation of mutated alleles of JAK2V617F [34][35][36] in the progression to PPV-MF and PET-MF, although we show here that allele burden did not impact on overall survival. We also report that CALR allele burden of PET-MF patients was significantly higher compared with a series of ET patients from our archives, indicating that a CALR allele burden greater than 50% is far more frequent in PET-MF than ET.…”
Section: Discussionsupporting
confidence: 83%
“…In a previous study [21], we found that MPL mutated ET patients had greater likelihood of transforming to PET-MF compared to other genotypes, but due to small number of events such difference did not reach the significance level; more recently, Elala et al reported shorter myelofibrosis-free survival in MPL mutated ET patients that remained significant in multivariate analysis, thereby corroborating our current findings [33]. On the other hand, results of this study validate and extend previous observations concerning the role of accumulation of mutated alleles of JAK2V617F [34][35][36] in the progression to PPV-MF and PET-MF, although we show here that allele burden did not impact on overall survival. We also report that CALR allele burden of PET-MF patients was significantly higher compared with a series of ET patients from our archives, indicating that a CALR allele burden greater than 50% is far more frequent in PET-MF than ET.…”
Section: Discussionsupporting
confidence: 83%
“…These observations are supported by recently published, retrospective series of 105 patients with PV. A higher JAK2 V617F allele burden correlated with more advanced myelofibrosis, greater splenomegaly and higher white blood cell count [Silver et al 2010]. Although a significant correlation with thrombosis risk could not be defined, there was a trend towards increased frequency of thrombosis as the JAK2 V617F allele burden increased.…”
Section: Introductionmentioning
confidence: 86%
“…However, in patients that are suspected to evolve to post-PV myelofibrosis (PPV-MF), I repeat the test to document accumulation of mutated alleles that usually accompanies transition to PPV-MF. [25][26][27][28] At present, there is no evidence that assessing other MPN-associated mutations 14 provides prognostic information, unlike in PMF patients. [29][30][31] I routinely order quantification of serum erythropoietin (sEPO) levels before phlebotomy is started to avoid fluctuations.…”
Section: At Presentationmentioning
confidence: 99%
“…Of note, in the proposed revised diagnostic criteria (Table 3 32 ), BM biopsy is mandatory because it helps differentiate early PV with concomitant thrombocytosis from ET, 33 and in patients with increased Hb levels, yet below the WHO threshold, BM biopsy may be diagnostic. 34 A grade 1 reticulin fibrosis is found in 15% of PV patients at baseline and does not imply an alternative diagnosis 27 ; however, patients with fibrosis may have a more advanced phase and be more prone to develop PPV-MF. 35 An abnormal karyotype has prognostic relevance.…”
Section: At Presentationmentioning
confidence: 99%